Effects of the freeze-thaw cycle on potential evapotranspiration in the permafrost regions of the Qinghai-Tibet Plateau, China - Liu, Xin; Yang, Wenjing; Zhao, Haipeng; Wang, Yibo; Wang, Genxu (Science of The Total Environment, 2019)
Potential evapotranspiration (ET0) is one of the important indicators for characterizing atmospheric evapotranspiration, but arduous observation conditions lead to a relative lack in the understanding of the ET0 mechanismin cold, high-elevation regions. The study of the sensitivity coefficient and contribution rate of meteorological elements to ET0 under the effects of the freeze-thaw cycle in the permafrost regions of the Qinghai-Tibet Plateau (QTP) showed that air temperature (T) and ET0 had similar change trends, which reached a peak during the summer thawing period (ST). Furthermore, analysis of meteorological elements in different freeze-thaw stages of the active layer soil revealed that the contribution rate of each meteorological element to ET0 showed a seasonal distinction. The sensitivity coefficient and contribution rate of the net radiation (R-n) and vapor pressure deficit (VPD) to ET0 were high, and their mean values were 0.52 and 0.44, respectively. In contrast, the sensitivity coefficient and contribution rate of wind speed (u(2)) and T to ET0 were very small, and the mean values of the sensitivity coefficient were 0.08 and 0.01, respectively. Additionally, T had the lowest contribution rate to ET0. These results indicated that permafrost had a stable regulatory effect on T. The results are expected to be helpful in developing a process-based frozen soil hydrological model. (C) (2019 Elsevier B.V. All rights reserved.